SITE 13 : RAJANG IMCA - James, Bali; Salvia, Diot; Ian Levi, Jackery; Wan Ruzzainie, Wan Arman; Dayang Amira, Fithriyaani; Cindy, Peter; Andrea, Chin; Vivien Yeo, Shu Jun; Belinda, Lip (WWF-Malaysia, 2024)
The proposed Rajang delta site is a subset of the larger part of Rajang delta covering Rajang, Belawai, Paloh and Bruit which serves as an important habitat for many species. The mangroves in the delta are unique with the most complex floristic composition compared to other mangrove areas in Sarawak as it consists of 14 subtypes of mangrove areas for migratory birds. The Rajang Delta is proposed to be considered as an EBSA, based on the results of a review for the criteria which indicates high rankings in five out of the seven criteria and medium rankings for the remaining two. Activities to initiate conservation and sustainable development in this area are also already in progress by respective agencies, hence providing a good supporting basis for the recommendation of the Rajang Delta to be included as a MyIMCA site.